NMR Studies of Transient Enzyme-Substrate Interactions - Lança Martins, Maria (2022)
"McoA is a hyperthermostable multicopper oxidase from Aquifex aeolicus with high oxidative power towards a wide range of natural aromatic compounds that holds great potential for biotechnological applications. McoA sets itself apart from other MCOs due to a highly flexible methionine rich long (Met-loop), located near the substrate-binding site and the T1-Cu catalytic center. Previous studies suggest that the Met-loop has a gatekeeping role, regulating substrate access to the binding pocket which is key for an efficient catalysis. We focused on McoA wild-type, a laccase-like variant (2F4) obtained through directed evolution, and their respective loop-truncated variants."